(S)-Perillaldehyde azine - Han, L.L.; Shi, J.H.; Yan, D.P.; Ng, S.W. (International Union of Crystallography, 2010)
The C = N-N = C linkage [torsion angle -172.5 (2)degrees] in the title azine, C20H28N2, adopts a trans conformation. The six-membered rings adopt sofa conformations.